Tycz Bär - starosta babimojski 1404-1407(?) = Tycz Bär - starost of Babimost 1404-1407(?) - Benyskiewicz, Krzysztof (1959- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper tells the story of the first starost of Babimost, Tycz Bär. The knight lived In Opalenica and came from a foreign family who arrived in Poland in the 14th century. At war Br was in his element. Before 1393, during one of his expeditions, Bär was taken prisoner. In order to regain his freedom, he had to mortgage his estate in Opalenica. King Władysław Jagiełło grantem him financial help to retrieve these goods. According to the customs of the Kingdom of Poland, Bär had to repay part of his debt serving in the king?s army.
Keywords: Tycz Bär; rycerstwo polskie; rycerstwo obce; lokalne elity rycerskie; genealogia; heraldyka; starostwo babimojskie; wojny polsko-krzyżackie; Jagiełło, Władysław (1362-1434); Polish knights; knights foreign; local noble elite; genealogy; heraldry; the county of Babimost; Polish-Teutonic War